Nemonoxacin achieved a better symptomatic improvement and a prolonged interval to next exacerbation than moxifloxacin for outpatients with acute exacerbations of chronic obstructive pulmonary disease - Weiwei Meng; Huihui Zeng; Zhiqi Zhao; Ruoyan Xiong; Yan Chen; Zhuo Li (Scientific Reports, 2023)
Abstract Nemonoxacin is a novel non-fluorinated quinolone with strong antibacterial efficacy, but data of its effect on acute exacerbations of chronic obstructive pulmonary disease (AECOPD) is rare. This study was conducted to compare the efficacy of oral nemonoxacin with moxifloxacin in AECOPD outpatients. In this retrospective observational study, a total of 101 AECOPD outpatients initially treated with nemonoxacin or moxifloxacin from July 2021 to March 2022 were enrolled. We collected COPD assessment test (CAT), Transition Dyspnea Indices (TDI) scores, and exacerbations information during 24 weeks follow-up from the electronic medical records. Kaplan–Meier curve was used to analyze the time to the next moderate/severe exacerbation. Compared to the moxifloxacin group, changes in CAT scores and TDI scores were significantly higher in the nemonoxacin group, and the nemonoxacin group also had a greater probability to reach the minimal clinically important difference of CAT (71.40% vs. 97.80%, p < 0.01) and TDI (40.50% vs. 60.00%, p < 0.05) at week 4. Despite no significant difference in the incidence of exacerbations between two groups, patients treated with nemonoxacin had a significantly prolonged time to next moderate/severe exacerbation than those with moxifloxacin (p < 0.05). Nemonoxacin achieved a better symptomatic improvement and a prolonged interval to next moderate/severe exacerbation for AECOPD outpatients.